2018
DOI: 10.1002/etc.4094
|View full text |Cite
|
Sign up to set email alerts
|

Fate, uptake, and distribution of nanoencapsulated pesticides in soil–earthworm systems and implications for environmental risk assessment

Abstract: Nanopesticides are novel plant protection products offering numerous benefits. Because nanoparticles behave differently from dissolved chemicals, the environmental risks of these materials could differ from conventional pesticides. We used soil-earthworm systems to compare the fate and uptake of analytical-grade bifenthrin to that of bifenthrin in traditional and nanoencapsulated formulations. Apparent sorption coefficients for bifenthrin were up to 3.8 times lower in the nano treatments than in the non-nano t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Given that the neonates used in this study are smaller than adults, a preferential uptake of particles under 500 nm is sensible and may result in increased ingestion of the SF when compared to the LF. One study found that nanoencapsulation increased the overall uptake of a pyrethroid in earthworms, but most of the active ingredient remained in the gut rather than being internalized [15]. If this were the case for the C. dubia , encapsulation could prevent a toxic response by preventing internalization of γ-cyhalothrin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the neonates used in this study are smaller than adults, a preferential uptake of particles under 500 nm is sensible and may result in increased ingestion of the SF when compared to the LF. One study found that nanoencapsulation increased the overall uptake of a pyrethroid in earthworms, but most of the active ingredient remained in the gut rather than being internalized [15]. If this were the case for the C. dubia , encapsulation could prevent a toxic response by preventing internalization of γ-cyhalothrin.…”
Section: Resultsmentioning
confidence: 99%
“…Further complicating our understanding of encapsulation technologies, capsules in the nanoscale (1–1000 nm) are garnering attention in pesticide literature [13,14,15,16] and have been observed in current-use formulations [17,18]. Nanoencapsulated formulas capitalize on the sheer diversity of nanomaterials available, including polymers, lipids, mesoporous silica, clay, and other materials [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The additional concerns and tests in risk assessment were suggested even all the ingredients of a certain nanoformulation was safe, because the nanopesticides with unique characteristics at nanoscale might have a distinct fate and behavior [ 1 ]. The evaluation of NCs toxicity still has difficulties and the toxicokinetics of NCs are also challenged [ 90 ]. Model predication on toxicokinetic might help us estimate toxic effects of NCs-delivered pesticides and other nanopesticides.…”
Section: Challenges and Perspectivementioning
confidence: 99%
“…The nanoformulation is able to significantly influence sorption and degradation phenomena determining pesticide fate and environmental impact [29]. Different micro-and nano-capsules have been formulated and commercialized for pesticides encapsulation and smart delivery [30,31]. Various types of nanomaterials are used as antibacterial agents aiming the substation of chemical pesticides in crops science [32].…”
Section: Nanopesticides and Sonication Technologymentioning
confidence: 99%